Awareness of periodontal disease and its management among medical faculty in Guntur district: A questionnaire-based study - Ravindranath Dhulipalla; Yamuna Marella; Alluri Juhee Keerthana; Harish Prabhu Dev Pillutla; Chaitanya Chintagunta; Tejaswin Polepalle (Wolters Kluwer Medknow Publications, 2016)
Aim: The aim of this study was to assess the awareness of periodontal disease, its influence on general health, and attitude toward periodontal disease management among medical faculty in Guntur district. Materials and Methods: In this cross-sectional study, 150 medical faculty members from different specialties in Guntur district were included in the study. A self-administered questionnaire was prepared based on knowledge, attitude, and practice surveys to assess the awareness of periodontal disease and its management. Results: Majority of the study participants (82%) had a previous dental visit. Only 31.3% believed that plaque is the major cause for periodontal disease. 56.7% responded that the relation between periodontal disease and systemic diseases is bidirectional. Only 39.3% were aware that periodontal disease is a risk factor for preterm low-birth weight infants. 52.6% of the medical faculty thought that scaling causes loss of enamel. 54.7% were aware that light amplification by stimulated emission of radiation is used in the periodontal treatment. Medical professionals who visited specialist in their previous dental visit obtained mean periodontal score (5.35 ± 1.686) greater than those who had visited general dentist and the difference is statistically significant (0.024). Conclusion: This study clearly demonstrates that medical practitioners had fair knowledge about various aspects of periodontal disease. This was particularly evident among those who have had a previous visit to a dentist. It was also found that young professionals with limited experience in the profession had better knowledge.